Corporate Social Responsibility Strategies of PT Sumber Alfaria Trijaya Tbk in Maintaining the Company's Image - Hildan Muhladin; Erna Febriani (Journal of Communication and Public Relations, 2025)
Corporate Social Responsibility represents a corporate commitment to improve social welfare and environmental sustainability that is beneficial to the institution and society. In public relations practice, CSR is often utilized as a strategic approach to improve and maintain corporate image. This study aims to examine the CSR strategies and tactics carried out by PT Sumber Alfaria Trijaya Tbk and to identify obstacles encountered in their execution. Adopting post-positivst paradigm, this research employs a descriptive qualitative method with a case study design. Data research was collected through in-depth interviews and analyzed using data reduction, data display and conclusion drawing techniques. The findings show that PT Sumber Alfaria Trijaya Tbk execute its CSR initiatives based on the Triple Bottom Line framework of profit, people and planet. Profit-oriented strategy conducted through Alfamart Care program, which focuses on donation fundraising, good donation, and blood donation event. People-oriented organized through Alfamart Smart and Alfamart SMEs, which provide education scholarship and facilitate marketing promotion for Small and Medium Enterprises using Alfamind Application. Planet-oriented strategy is carried through Alfamart Clean and Energy, emphasizing plastic reduction campaigns and tree-planting activities to support environmental conservation and disaster mitigation. However, the implementation of CSR faces challenges, especially ineffective communications channel that limit the dissemination of innovation-related information to heterogenous publics. This study underscores the critical role of CSR generate sustain reputational value rather than symbolic event only.